Dissemination/Communication Report. Period concerning this report: 01.01.2018-31.12.2018. - Glaskova-Kuzmina, Tatjana (Zenodo, 2018)
During the first year of the project implementation different dissemination/communication activities were carried out. First scientific results were presented on the 18th European Conference on Composite Materials (ECCM). For the dissemination of information among general public professional FACEBOOK profile was developed. Additionally, for better dissemination of project scientific results project profile “Environmental effects on physical properties of smart composites and fibre-reinforced plastics modified by carbonaceous nanofillers for structural applications” was developed at open-access database ZENODO (www.zenodo.org) under community POSTDOC-Latvia providing open-access to all published materials. Both profiles will be regularly updated with actual project results during full project implementation period.
Keywords: Dissemination/Communication Report; POSTDOC Latvia; project implementation; Research Subject Categories::TECHNOLOGY